A guide to adhesion GPCR research. (17th November 2021) - Liebscher, Ines; Cevheroğlu, Orkun; Hsiao, Cheng‐Chih; Maia, André F.; Schihada, Hannes; Scholz, Nicole; Soave, Mark; Spiess, Katja; Trajković, Katarina; Kosloff, Mickey; Prömel, Simone
Abstract : Adhesion G protein‐coupled receptors (aGPCRs) are a class of structurally and functionally highly intriguing cell surface receptors with essential functions in health and disease. Thus, they display a vastly unexploited pharmacological potential. Our current understanding of the physiological functions and signaling mechanisms of aGPCRs form the basis for elucidating further molecular aspects. Combining these with novel tools and methodologies from different fields tailored for studying these unusual receptors yields a powerful potential for pushing aGPCR research from singular approaches toward building up an in‐depth knowledge that will facilitate its translation to applied science. In this review, we summarize the state‐of‐the‐art knowledge on aGPCRs in respect to structure–function relations, physiology, and clinical aspects, as well as the latest advances in the field. We highlight the upcoming most pressing topics in aGPCR research and identify strategies to tackle them. Furthermore, we discuss approaches how to promote, stimulate, and translate research on aGPCRs 'from bench to bedside' in the future. Abstract : Adhesion G protein‐coupled receptors (aGPCRs) are unique cell surface molecules with extraordinary structural and functional features. They are essential in health and disease and, thus, of great interest to scientists, pharmaceutical industry, and clinicians. Although huge progress has been made in recent years to unravel their functions, research on aGPCRs is only beginning to take shape and novel avenues and directions are essential to extend our knowledge.